Local Bankruptcy and Geographic Contagion in the Bank Loan Market - Addoum, Jawad M; Kumar, Alok; Le, Nhan; Niessen-Ruenzi, Alexandra (Review of Finance, 2020)
Abstract We examine whether corporate bankruptcies influence bank loan characteristics of geographically proximate firms. Controlling for industry contagion and local economic conditions, firms headquartered near a bankruptcy event experience a 7 basis point increase in loan spreads. The effect is transitory and cannot be fully explained by local correlated information or lenders’ financial health. Instead, the effect is more pronounced for informationally opaque bankruptcies and borrowers, and weakened among loans with relationship lenders and lenders with significant local presence.